Algorithm-Based Fault Tolerance Applied to P2P Computing Networks - Roche, T.; Cunche, M.; Roch, J.-L. (2009 First International Conference on Advances in P2P Systems, 2009)
P2P computing platforms are subject to a wide range of attacks. In this paper, we propose a generalisation of the previous disk-less checkpointing approach for fault-tolerance in high performance computing systems. Our contribution is in two directions: first, instead of restricting to 2D checksums that tolerate only a small number of node failures, we propose to base disk-less checkpointing on linear codes to tolerate potentially a large number of faults. Then, we compare and analyse the use of low density parity check (LDPC) to classical Reed-Solomon (RS) codes with respect to different fault models to fit P2P systems. Our LDPC disk-less checkpointing method is well suited when only node disconnections are considered, but cannot deal with byzantine peers. Our RS disk-less checkpointing method tolerates such byzantine errors, but is restricted to exact finite field computations.